2022
DOI: 10.3390/nu14102118
|View full text |Cite
|
Sign up to set email alerts
|

Comment on Keeler et al. Ketamine as a Treatment for Anorexia Nervosa: A Narrative Review. Nutrients 2021, 13, 4158

Abstract: Anorexia Nervosa (AN) represents a difficult therapeutic challenge, with up to 4% prevalence among females and increasing incidence among youth [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Taken together, we agree with Skokou [ 2 ] that the glutamate system might be highly relevant for the treatment of eating disorders. As explained in our previous paper [ 1 ], we particularly believe that ketamine might lead to a breakthrough in the pharmacological treatment of AN.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Taken together, we agree with Skokou [ 2 ] that the glutamate system might be highly relevant for the treatment of eating disorders. As explained in our previous paper [ 1 ], we particularly believe that ketamine might lead to a breakthrough in the pharmacological treatment of AN.…”
supporting
confidence: 92%
“…In response to our narrative review, which suggested the use of the glutamatergic n-methyl-D-aspartate (NMDA) receptor antagonist ketamine as a potential treatment for anorexia nervosa (AN) [ 1 ], Maria Skokou posed the question whether other glutamatergic medications (e.g., lamotrigine) might be effective in the treatment of eating disorders in general [ 2 ]. Therefore, we would like to develop the idea further that the glutamate system might be of relevance for the pathophysiology and the treatment of eating disorders.…”
mentioning
confidence: 99%
See 1 more Smart Citation